2011
DOI: 10.2478/s11772-011-0021-7
|View full text |Cite
|
Sign up to set email alerts
|

Determination of energy difference and width of minibands in GaAs/AlGaAs superlattices by using Fourier transform photoreflectance and photoluminescence

Abstract: In this work, Fourier transform photoreflectance (in a form of fast differential reflectance spectroscopy) has been used to study the interband optical transitions in molecular beam epitaxially grown GaAs/AlGaAs superlattices. The dependence of the measured features on the growth parameters (QW and barrier widths) has been studied. The minibands widths and energy differences between them have been obtained and matched to these coming from effective mass calculations. In addition, it has been shown that Fourier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Dashed lines represent the transition energies obtained from numerical calculations (where h(n)e(n) or l(n)e(n) notations means heavy (light) hole n-th level and electron n-th level). In this layout of superlattices layers designed as a QCL active region and injector, the energy width of the minibands is negligible, as distinct from the typical superlattices where and points related optical transitions might be observed (Motyka et al 2011b). There is a difference between ground state transition energies obtained from these two experiments (PR and PL), which can be better seen in Fig.…”
Section: Resultsmentioning
confidence: 88%
“…Dashed lines represent the transition energies obtained from numerical calculations (where h(n)e(n) or l(n)e(n) notations means heavy (light) hole n-th level and electron n-th level). In this layout of superlattices layers designed as a QCL active region and injector, the energy width of the minibands is negligible, as distinct from the typical superlattices where and points related optical transitions might be observed (Motyka et al 2011b). There is a difference between ground state transition energies obtained from these two experiments (PR and PL), which can be better seen in Fig.…”
Section: Resultsmentioning
confidence: 88%
“…The dynamical diffraction theory has been used for simulating the symmetric (004) reflections leading to the extraction of structural parameters of periodic structures. An almost perfect planar uniformity of growth condi− tions of the "slow−grown" structures was proved by the photoluminescence (PL) and photoreflectance (PR) charac− terisation that was performed for superlattice test structures [16][17][18].…”
Section: Ex Situ Examinationmentioning
confidence: 99%
“…Previously, we reported that photoluminescence (emission) and photoreflectance (high sensitivity absorption-like modulation technique), realized within a Fourier-transform (FT) spectrometer-based experimental configuration [11], can provide the information about the electronic structure of the AlGaAs/GaAs superlattices due to the possibility of detecting the interband and intersubband optical transitions [12]. Furthermore, these techniques were successfully employed to examine the growth rates accuracy by the analysis of the Stokes shift between the emission and absorption spectra of the active region of a mid-infrared QCL (at approx.…”
Section: Introductionmentioning
confidence: 99%